The development of cortical processing of speech differs between children with cochlear implants and normal hearing and changes with parental singing - Torppa, Ritva; Kuuluvainen, Soila; Lipsanen, Jari (Frontiers in Neuroscience, 2022)
Objective: The aim of the present study was to investigate speech processing development in children with normal hearing (NH) and cochlear implants (CI) groups using a multifeature event-related potential (ERP) paradigm. Singing is associated to enhanced attention and speech perception. Therefore it’s connection to ERPs was investigated in the CI group. Methods: The paradigm included five change types in a pseudoword: two easy- (duration, gap) and three difficult-to-detect (vowel, pitch, intensity) with CIs. The positive mismatch responses (pMMR), mismatch negativity (MMN), P3a and late differentiating negativity (LDN) responses of preschoolers (below 6 y 9 m) and schoolchildren (above 6 y 9 m) with NH or CIs at two time points (T1, T2) were investigated with Linear Mixed Modelling (LMM). For the CI group, the association of singing at home and ERP development was modelled with LMM. Results: Overall, responses elicited by the easy- and difficult to detect changes differed between the CI and NH groups. Compared to the NH group, the CI group had smaller MMNs to vowel duration changes and gaps, larger P3a responses to gaps, and larger pMMRs and smaller LDNs to vowel identity changes. Preschoolers had smaller P3a responses and larger LDNs to gaps, and larger pMMRs to vowel identity changes than schoolchildren. In addition, the pMMRs to gaps increased from T1 to T2 in preschoolers. More parental singing in the CI group was associated with increasing pMMR and less parental singing with decreasing P3a amplitudes from T1 to T2. Conclusions: The multifeature paradigm is suitable for assessing cortical speech processing development in children. In children with CIs, cortical discrimination is often reflected in pMMR and P3a responses, and in MMN and LDN responses in children with NH. Moreover, the cortical speech discrimination of children with CIs is develops late, and over time and age, their speech sound change processing changes as does the processing of children with NH. Importantly, multisensory activities such as parental singing can lead to improvement in the discrimination and attention shifting towards speech changes in children with CIs. These novel results should be taken into account in future research and rehabilitation.